Ecological footprint of Municipality Maribor - Tjukajev, Patricija (Journal for Geography, 2017)
Protecting the environment and preserving nature are today’s indispensable topics when it comes to the future of man on Earth. A modern society tackles this problem with a wide range of research and measures to improve or at least preserve the state of the environment. Solving the state of the environment can be addressed at different levels, based on various surveys, of which the more popular method is the ecological footprint. This method shows us how much environmental resources we have, compared to how much we use. The article presents the calculation of the ecological footprint on the example of the Municipality of Maribor, since this method of geographical research in the municipality has remained intact until today. The results of this case provide concrete measures to reduce the pressures on the environment in the municipality, while at the same time not neglecting the economic and social interests of the municipality. Due to the modest methodology of data collection in the Municipality of Maribor, all the insufficient data that are necessary for the calculation of the ecological footprint and could be useful in the future are presented.
Keywords: Municipality Maribor; biocapacity; ecological footprint; ecological deficit; sustainable development